Tata Laksana Fraktur Panggul pada Geriatri: Sudut Pandang Internis - Jannah, Laila M; Dwimartutie, Noto (Jurnal Penyakit Dalam Indonesia, 2025)
Hip fracture are a common issue in geriatric patients, associated with increased risk of morbidity and mortality. The complex and multimorbid characteristics of geriatric patients presents significant challenge in their management. Optimal outcomes require a comprehensive interdisciplinary approach to care, aiming to restore functional status and reduce postoperative complications. A holistic strategy, grounded in thorough Comprehensive Geriatric Assessment (CGA), is essential to guide individualized treatment and ensure effective, patient-centered management.